SANDALWOOD (SANTALUM ALBUM): ANCIENT TREE WITH SIGNIFICANT MEDICINAL BENEFITS (International Journal of Ayurveda and Pharma Research, 2021)
Santalum album L. is commonly known as East Indian sandalwood, Shrigandha, sandalwood and Chandana. The plant is considered as the oldest, precious and commercially significant herbal plant which is also used as timber in India. The plant is well known for its unique and distinctive fragrance. Also, this plant is considered sacred and its importance and usage are also mentioned in Vedas, Puranas, Buddhism, epics and scriptures. It is used in various religions like Hindu, Buddhism and Jainism culture for auspicious work. The heartwood of the plant is very expensive and is associated with great commercial value in the national and international market as it is enriched with fragranced essential oil. The aromatic essential oil of the plant is used in various perfumes, food products, cosmetics, aromatherapy and pharmaceutical industries. Traditionally, the plant is used in various medicinal systems such as Ayurveda, Unani and Siddha to cure diseases like jaundice, dysentery, gastric irritability and is used as a tonic for liver, heart, fever, memory improvement, anti-poison and for blood purifier. In Ayurveda, the sandalwood plant is used as an expectorant, diuretic, astringent, stimulant, coolant and sedative agent. Besides this, the plant is associated with reported therapeutic and pharmacological properties such as antioxidant, anticancer, anti-inflammatory, antiviral, antibacterial, antifungal, hepatoprotective and cardio-protective properties. Although, due to the overexploitation of the plant it is enlisted in the IUCN Red List. In this review, the traditional medicinal usage of the sandalwood plant and its pharmacological properties along with its modern view is briefly described.